Reducing electrode wear using cryogenic cooling during electrical discharge machining - Abdulkareem, Suleiman; Ali Khan, Ahsan; Konneh, Mohamed (Trans Tech Publications, Switzerland, 2010)
In electrical discharge machining (EDM), material is removed by a series of electrical discharge between the electrode (tool) and the workpiece that develops a temperature of about 8,0000C to 12,0000C. Due to high temperature of the sparks, work material is melted and vapourized, at the same time the electrode material is also eroded by melting and vapourization. Electrodes wear (EW) process is quite similar to the material removal mechanism as the electrode and the workpiece are considered as a set of electrode in EDM. In the present study effort has been made to reduce EW by cooling, using liquid nitrogen during the EDM of titanium alloy. Investigation on the effect of cooling on electrode wear (EW), material removal rate (MRR) and surface roughness (Ra) of the workpiece was carried out. Current (I), pulse on-time (ton), pause offtime (toff) and voltage (v) were considered as the machining parameters. Design of experiment (DOE) was used to design the experimental works. Cooling of electrode by this technique reduced the melting and vapourization of electrode material and enhances electrode life. It was possible to reduce EW up to 27% by applying this technique while MRR and Ra were improved by 18% and 8% respectively.